Bioactive Constituent Profiling of Poly Herbal Distillate Thiribhaladi Dravagam to Evaluate Its Credible Therapeutic Role in Siddha Clinical Practices - S, Vinayak; R, Gayatri; Wilson, Eugene; Rajkumar, Shyamala; Kumar, K.N Sunil; Selvarajan, S.; K, Kanakavalli (Asian Journal of Pharmaceutical Research and Development, 2020)
Introduction: Hydro distillation in Siddha medicine is the technique of extracting valuable principles from a pre-processed raw drug through the traditional process of distillation under a controlled temperature setting. Thiribhaladi Dravagam (TD) is one of the polyherbal distillate formulation stated in the Tamil medical text specified for phlegmatic affections. The drug was subjected to GC-MS studies to screen its bioactive sketch. Methods: Two sets of raw drug samples from different locations were collected. The raw drugs were purified and pre-processed as per the classical literature and distilled in a traditional apparatus. Two distillate samples (TD 1 & TD 2) were prepared from the set of ingredients and were screened for its constituents. Results: The Gas chromatogram of TD 1 revealed 4 prominent peaks with retention time ranging from 4.84 to 8.27. TD 2 reported 8 prominent peaks with retention time ranging from 3.35 to 7.88. The study testified the presence of active volatile metabolites like aldehydes and oxygenated monoterpenes like citral and borneol, monocyclic alcoholic compounds like terpineol and organic acids like caprylic acid from both the samples. TD 2 reported more pharmacologically valuable lead molecules than TD 1, which may be due to the variation in diversity of the two sets of raw drug samples. Conclusion: The bio constituents of TD was found to be pharmacologically significant from the review of various reputed research works supporting the traditional claim on its role in the respiratory system and for maintaining good health. Through the review of Thiribhaladi Dravagam and its analytical part performed through GC-MS, the medical applications of TD in multiple clinical associations and as a perfect health promoter has been justified for promoting its traditional value.